2007
DOI: 10.1097/yct.0b013e31806db4dd
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Maintenance Electroconvulsive Therapy for Treatment of Psychotic Depression in a Pregnant Patient

Abstract: Depression may relapse during pregnancy in women with a history of depression. Treatments which may be effective for mothers may be harmful to the fetus. Electroconvulsive therapy (ECT) has been widely used in patients with different medical illnesses. It is safe, and its efficacy is well established. In our example, the patient was a 34-year-old white woman who was at 13 weeks' gestation at the time of admission to our hospital. Over a 1-month period, the patient underwent a total of 13 ECTs (3 times a week) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The electroconvulsive current does not pass through the uterus [69,70], and so other physiological and pathophysiological factors have to be considered as causes for this problem. Some studies propose that ECT can increase the risk of fetal and maternal cerebral hemorrhage and bronchospasm and cardiac events during pregnancy [71,72]. However, other authors disagree on this [73].…”
Section: Discussionmentioning
confidence: 96%
“…The electroconvulsive current does not pass through the uterus [69,70], and so other physiological and pathophysiological factors have to be considered as causes for this problem. Some studies propose that ECT can increase the risk of fetal and maternal cerebral hemorrhage and bronchospasm and cardiac events during pregnancy [71,72]. However, other authors disagree on this [73].…”
Section: Discussionmentioning
confidence: 96%
“…b Indicates ECT-related or ECT-linked adverse event. (14,40,45,52,57,60,61,65). Pinette and colleagues (68) recently reported on an infant whose mother underwent multiple rounds of ECT, the first being around the time of conception.…”
Section: Adverse Events Fetal Adverse Eventsmentioning
confidence: 97%
“…It has been suggested that ECT in pregnant patients increases the risk of fetal and maternal cerebral hemorrhage, and that ECT also increases the risk of bronchospasm and cardiac events during pregnancy (65,86). Most of these concerns have been refuted by the available evidence (87).…”
Section: Other Adverse Eventsmentioning
confidence: 97%
See 1 more Smart Citation
“…5,6 In addition, the mother may be vulnerable to medication adverse effects related to the physiologic changes of pregnancy. 7 At the same time, it is known that untreated depression in pregnancy is associated with increased risks of poor maternal self care, 3 substance abuse, and premature labor. 2,4,8,9 Electroconvulsive therapy (ECT) has been used safely and effectively as a treatment of depression in all 3 trimesters of pregnancy.…”
mentioning
confidence: 99%